Anxiety among Central American Migrants in Mexico: A Cumulative Vulnerability - Gorn, Shoshana Berenzon; Saavedra, Nayelhi; Bojorquez, Ietza; Reed, Geoffrey; Wainberg, Milton L.; Medina-Mora, María Elena (International journal of environmental research and public health, 2023)
Migration exposes Central American migrants, particularly those who migrate without documents, to a range of incidents, dangers, and risks that increase their vulnerability to anxiety symptoms. In most cases, the poverty, conflict, and violence they experience in their countries of origin are compounded by the unpredictable conditions of their journey through Mexico. The objective of this study was to explore the association between the presence of emotional discomfort and the experience of various vulnerabilities from the perspective of a group of Central American migrants in transit through Mexico. This is a descriptive, mixed-methods study (QUALI-QUAN). During the qualitative phase, thirty-five migrants were interviewed (twenty in Mexico City and six in Tijuana). During the quantitative phase, a questionnaire was administered to 217 migrants in shelters in Tijuana. An analysis of the subjects’ accounts yielded various factors associated with stress and anxiety, which were divided into five main groups: (1) precarious conditions during the journey through Mexico, (2) rejection and abuse due to their identity, (3) abuse by Mexican authorities, (4) violence by criminal organizations, and (5) waiting time before being able to continue their journey. The interaction of various vulnerabilities predisposes individuals to present emotional discomfort, such as anxiety. Migrants who reported experiencing three or more vulnerabilities presented the highest percentages of anxiety symptoms.